DEVELOPING THE SKILLS OF 5TH–8TH GRADE STUDENTS IN UNDERSTANDING THE GRAMMATICAL FEATURES OF UZBEK AND ENGLISH CONJUNCTIONS: METHODOLOGIES AND TEACHING CHALLENGES - Zafarajon Nazarov Abdullajon o’g’li; Erkulova Feruza Melikuziyevna (World Scientific Research Journal, 2025)
This paper explores methodologies for enhancing the grammatical understanding of conjunctions in both Uzbek and English among students in grades 5 to 8. Emphasis is placed on comparative grammar instruction, contextual usage, and interactive teaching strategies to build cross-linguistic awareness. The study also identifies common challenges faced in English language lessons and offers pedagogical solutions for improving teaching outcomes in multilingual classrooms.